Writing Interventions for High School Students With Disabilities: A Review of Single-Case Design Studies. (November 2014) - Cook, Kathleen B.; Bennett, Katie E.
Proficiency in writing increases opportunities in higher education, employment, and social relationships. Many students in the United States, however, are struggling writers. In particular, the writing performance of students with disabilities in secondary grades continues to lag behind grade level peers. The purpose of this article was to review writing interventions for high school students with disabilities to identify those practices that have been shown to be effective in supporting writing development. All studies were peer-reviewed, employed a single-case experimental design, and evaluated writing interventions used with students with disabilities in Grades 9 through 12. We used the What Works Clearinghouse (WWC) single-case design standards (Kratochwill et al., 2010) to evaluate the effects of writing interventions in the 14 identified studies. Specific interventions included Self-Regulated Strategy Development (SRSD), Expressive Writing ™ (Direct Instruction), Cognitive Strategy Instruction in Writing, and pentop computers. Results indicated that only two SRSD programs and the pentop computer program demonstrated strong or moderate effects on written expression in studies that met WWC evidence standards with reservations.